An Experimental Examination of Thermal Conductivity Anisotropy in hcp Iron - Ohta, Kenji; Nishihara, Yu; Sato, Yuki; Hirose, Kei; Yagi, Takashi; Kawaguchi, Saori I.; Hirao, Naohisa; Ohishi, Yasuo (Frontiers in Earth Science, 2018)
The Earth's core mainly consists of iron, and its thermal transport properties are of vital importance for our understanding of the thermal evolution and the dynamics of the core and the mantle. However, the reported values of thermal conductivity of iron at the core conditions are so far inconclusive. Although hexagonal closed-packed (hcp) iron is often studied as a proxy metal to investigate the physical properties not only of the inner core, but also the outer core, the anisotropy of the thermal conductivity of hcp iron has never been experimentally examined. Here we report the results of texture analyses by means of synchrotron X-ray diffraction experiments and thermal conductivity measurements on polycrystalline hcp iron up to 44.5 GPa and 300 K. These results indicate that the thermal conductivity of single crystal hcp iron along c axis is about 3–4 times higher than that along a axis, which could have partially caused the controversial values of the thermal conductivity of hcp iron at the Earth's core conditions.